IMPLEMENTATION OF PAIRED CORRELATION AND REGRESSION ANALYSIS BETWEEN THE NUMBER OF BIRTHS AND THE NUMBER OF MARRIAGES IN THE REPUBLIC OF UZBEKISTAN BY REGION IN 2021 - Shukurov Ikrom Abdurashitovich; Kamoljonova Mehrangiz Askarovna (Zeta Repository, 2023)
In this article, in order to analyze the demographic situation of the population of the Republic of Uzbekistan, the correspondence between the number of births in 2021 and the number of marriages concluded in 2021 is analyzed. As a result of the analysis, a regression equation of the relationship between the two indicators was created, and based on the analysis, scientifically based suggestions and comments were given.